Possible chondroprotective effect of canakinumab: An in vitro study on human osteoarthritic chondrocytes. Issue 2 (February 2015) - Cheleschi, Sara; Cantarini, Luca; Pascarelli, Nicola Antonio; Collodel, Giulia; Lucherini, Orso Maria; Galeazzi, Mauro; Fioravanti, Antonella
Highlights Canakinumab is a human IgGκ monoclonal antibody that neutralizes the IL-1β. OA chondrocytes incubated with canakinumab alone or with TNF-α for 48 h. Canakinumab counteracts the negative effects of TNF-α on OA chondrocyte cultures. Our experiments confirmed the protective role of canakinumab. The canakinumab may have a potential chondroprotective role in OA.